2015
DOI: 10.1068/b130102p
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Landscape of Overruns in Transport Infrastructure Projects

Abstract: Cost and schedule overruns are endemic features of transport infrastructure projects. Despite the considerable amount of research within the field of transport and planning in the past thirty years, limited progress has been made to improving the performance of projects. We contend that this will continue to be an issue as long as research efforts focus on the ‘outside view’ with emphasis being placed upon strategic misrepresentation and optimism bias. Understanding ‘why’ and ‘how’ projects overrun, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 79 publications
2
42
0
2
Order By: Relevance
“…Given the uncertainty and structural complexity, the use of deterministic historical cost database to estimate the cost of construction is not justifiable (Nguyen et al 2008). Love et al (2015) state that a base estimate (deterministic) plus the contingency figure typically form a project's estimated costs. Contingency can be defined as "the amount of funds, budget, or time needed above the estimate to reduce the risk of overruns of project objectives to a level acceptable for the organization" (PMI 2011).…”
Section: Conceptual Cost Estimation In Tvdmentioning
confidence: 99%
“…Given the uncertainty and structural complexity, the use of deterministic historical cost database to estimate the cost of construction is not justifiable (Nguyen et al 2008). Love et al (2015) state that a base estimate (deterministic) plus the contingency figure typically form a project's estimated costs. Contingency can be defined as "the amount of funds, budget, or time needed above the estimate to reduce the risk of overruns of project objectives to a level acceptable for the organization" (PMI 2011).…”
Section: Conceptual Cost Estimation In Tvdmentioning
confidence: 99%
“…That is, the plan to achieve greater goals cannot be more important than giving a commitment to planning. It is also important to learn to separate politics from projects, not the least the need to evaluate project ambitions objectively (see Love et al, 2015). It was enough troubles that commitments were given to the project while exploratory investigations on crucial raw materials were not yet concluded.…”
Section: Project Leadershipmentioning
confidence: 99%
“…In Flyvbjerg et al's (2013) view, client's opinions are sacrosanct: Opinions at variance are either deceptive or delusional. Love et al (2015) have provided an idealist view. They suggest variabilities are a constant feature of complex projects and that such projects deserve holistic consideration of issues such as clear integration between leadership and project systems.…”
Section: Socrates' Generic Management and Leadership Theorymentioning
confidence: 99%
“…Cost overruns have been and continue to be the bête noire for the public sector in Australia (Love et al, 2015a;Love et al, 2017a;; this also is a problem worldwide (Flyvbjerg et al, 2002;Cantarelli et al, 2012;Odeck, 2014). Cantarelli et al (2012) has revealed that the size of the cost overrun that can materialize (i.e., from the decision to build to a project's practical completion) varies by geographical region.…”
Section: Introductionmentioning
confidence: 99%